Transferring the control over sub-district health promoting hospital from the Ministry of Public Health to the provincial administration organization, a case study in Phitsanulok - Narattharaksa, Kanida; Sirilak, Supinda; Sirilak, Piya; Narattharaksa, Teeradej (Journal of Medical and Public Health Region 4, 2024)
Phitsanulok Provincial Administrative Organization (PPAO) was carried out with 3 objectives 1) To determine relevant laws on such transfer 2) To determine problems and obstacles pertaining to implementation of such laws 3) To provide recommendations on amendments of such laws to enable such transfer more efficiently. According to the Mechanisms and Processes on Decentralization to Local Administrative Organization Act BE 2542, sub-district health stations have been transferred to be under the control of the Phitsanulok Provincial Administrative Organization from the Ministry of Public Health as of October 2023. Methodologies are 1) Content analysis and inference on existing relevant laws and regulations 2) In-depth interviews involving relevant personnel using thematic analysis 3) Group discussions involving administrative personnel from the PAO, the Provincial Health Office, and sub-district health stations of the Phitsanulok province, and 4) Presentations and inquiries for opinions on the results of the study from officials at both the policy setting and operational levels. Findings are 1) PAO duties and powers on the existing acts, announcements, rules and regulations, letters of notification, memorandums of understanding, interagency agreements, and relevant operational manuals, there were problems and issues in how to interpret and implement them in a unified manner 2) Measures to encourage all relevant public agencies to implement pertinent policies and procedures within specific timeframes were lacking, 3) Lack of communications to relevant personnel to obtain positive attitudes towards such transfer. This study provides policy recommendations on various issues regarding the need for legal reform including relevant issues, coordination and cooperation between a given POA and relevant local administrative organizations, alternative approaches on public health promotion, memorandums of understanding between central government, rules and regulations on personnel administration, and acquisition of medicine and medical supplies by the PAO, etc.